2013
DOI: 10.1590/s0100-736x2013000700012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to sublethal concentrations of sodium cyanide on the carbohydrate metabolism of the Indian Major Carp Labeo rohita (Hamilton, 1822)

Abstract: Experiments were designed to study in-vivo effects of sodium cyanide on biochemical endpoints in the freshwater fish Labeo rohita. Fish were exposed to two sublethal concentrations (0.106 and 0.064mg/L) for a period of 15 days. Levels of glycogen, pyruvate, lactate and the enzymatic activities of lactate dehydrogenase (LDH), succinate dehydrogenase (SDH), glucose-6-phosphate dehydrogenase (G6PDH), phosphorylase, alkaline phosphatase (ALP), acid phosphatase (AcP) were assessed in different tissues (liver, muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…This could have been the result of stress caused by residual dietary cyanide. Dube et al (2013) reported a significantly elevated LDH in liver, muscle and gill of L. rohita exposed to sublethal concentrations of cyanide. They attributed the increased tissue LDH to a switchover of metabolic pathways towards compensatory mechanisms, a situation that cannot be ruled out under current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This could have been the result of stress caused by residual dietary cyanide. Dube et al (2013) reported a significantly elevated LDH in liver, muscle and gill of L. rohita exposed to sublethal concentrations of cyanide. They attributed the increased tissue LDH to a switchover of metabolic pathways towards compensatory mechanisms, a situation that cannot be ruled out under current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium cyanide caused steady decreased with time in different enzymatic activities such as succinate dehydrogenase, lactate dehydrogenase, phosphorylase, glucose-6-phosphate dehydrogenase, acid phosphates and alkaline phosphatase in different tissues such as liver, gills and muscles of Labeo rohita (Dube et al, 2013) and catalase in Cyprinus carpio (David et al, 2008). Many other studies are depicting pesticides as inducer of anomalous biochemical changes in fish ( Joshi et al, 1981;Swetharanysm, 1991;Silvia et al, 1994;Anusha et al, 1996;Cookson and Pentreath, 1996;Geetha et al, 1999;Luther et al, 1999;Kamble and Muley, 2000;Jiraungkoorskul et al, 2003;Shankar et al, 2005;Milaeva, 2006;Neto et al, 2008;Nwani et al, 2010;Muthukumaravel et al, 2013).…”
Section: Pesticide Induced Biochemical Changes/ Oxidative Stress In Fishmentioning
confidence: 99%
“…David and Kartheek [8] found decreases in catalase, superoxide dismutase, glutathione peroxidase, and glutathione S-transferase activities in carp fish to which they applied sodium cyanide at a concentration of 0.1 mg/L for 10 and 20 days compared to the control group. For another freshwater fish species, Labeo rohita, it was reported that ATPase enzyme was inhibited in lethal (0,32 mg/L) and sublethal (0,064 mg/L) concentrations [9]; glycogen and pyruvate amounts decreased at sublethal (0,106 ve 0,064 mg/L) concentrations [10]; the levels of structural and soluble protein decreased at sublethal (0,2 mg/L) concentration [11]. Bonanno et al, found that blood thiocyanate levels in Amphiprion clarkii, to which they applied 50 ppm cyanide for 20 and 45 seconds, reached levels of 301 -468 ppb [12].…”
Section: Introductionmentioning
confidence: 99%